Antioxidant Capacity and Disease Resistance Enhanced by Dietary D-Glucuronolactone Supplementation in Chinese Soft-Shelled Turtles (Pelodiscus sinensis) - Tong Zhou; Wenyi Wu; Mingyang Xue; Yong Zhou; Hongwei Liang; Wei Liu (Antioxidants)
D-glucuronolactone (DGL), a hepatoprotective compound widely used in clinical and energy products, was evaluated for its effects on Chinese soft-shelled turtles (Pelodiscus sinensis) through an 8-week feeding trial with dietary supplementation (0, 200, and 400 mg kg−1). DGL did not alter survival or feed intake, but induced dose-dependent growth improvements, including increased final body weight, weight gain rate, specific growth rate, and muscle/liver glycogen, alongside reduced feed conversion ratio and muscle and liver fat. Serum analysis showed decreased activities of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and reduced low-density lipoprotein cholesterol, total cholesterol, and triacylglycerols. Antioxidant indices revealed elevated catalase and superoxide dismutase (SOD) activities in serum and intestine, coupled with reduced malondialdehyde, though hepatic SOD activity declined. Histologically, 400 mg kg−1 DGL alleviated liver lesions without impacting intestinal morphology. Molecular analyses demonstrated upregulated muscle mTOR signaling genes (mTOR, IGF1, S6K1) but downregulated hepatic/intestinal mTOR and IGF1 expression. DGL also suppressed inflammatory cytokines (TNF-α, IL-1β, IL-10) in liver and intestine. Challenge tests with Aeromonas hydrophila confirmed the enhanced disease resistance in DGL-supplemented turtles. These findings highlight DGL’s potential as a nutritional strategy to enhance growth, antioxidant capacity, and health in intensive turtle farming.